Hubungan Pola Asuh Orang Tua dengan Perilaku Kenakalan Remaja di SMAN 1 Sirah Pulau Padang - Sandra Putra, Riko; Mutmainah, Mutmainah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Parenting styles represent the interaction between parents and children, reflecting parental attitudes, methods, and behaviors in educating and guiding their offspring. This study aims to investigate the relationship between parenting styles and adolescent delinquency at SMAN 1 Sirah Pulau Padang. A quantitative approach was employed, utilizing a descriptive cross-sectional survey design. A sample of 79 adolescents was selected through a random sampling technique. The instruments used included the Parenting Style and Dimensions Questionnaire (PSDQ) to assess parenting styles and the Self-Report Delinquency Scale (SRD) to evaluate delinquent behavior.Data analysis was conducted using the Spearman Rank correlation test. The results indicated that the majority of adolescents (n=34, 43%) experienced authoritative parenting, while the level of adolescent delinquency was predominantly in the low category (n=73, 92.4%). Statistical analysis revealed a significant correlation between parenting styles and adolescent delinquency (p < 0.05), suggesting that balanced parenting styles tend to reduce deviant behavior in adolescents. Based on these findings, it is recommended that parents implement consistent, attentive, and child-centered parenting to prevent delinquency. This research may serve as a foundation for future studies to examine other factors influencing adolescent delinquent behavior